Respite and repair: how mothers of incarcerated long-term problematic drug users make prison work for them. (3rd July 2016) - Cartwright, Luke
Abstract: This article considers the way a group of mothers experienced the incarceration of their problematic drug using offspring. The offspring had been imprisoned for a range of offences including theft, burglary and drug dealing with the root cause of their incarceration being connected to their long-term problematic drug use. Much of the existing literature on imprisonment identifies the separation of offenders from their family as a source of strain both for the offender and the family, with separation being one of the pains of imprisonment described in the literature. However, in contrast to this, the evidence gathered during the research that this article is based upon, highlights how the mothers of problematic drug users sought to use the periods of time their offspring were in prison as respite from their difficult and time-consuming caring responsibilities. Furthermore, the time their offspring were incarcerated was used to repair fractured relationships.